IMPROVING PRODUCT QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AT CINCAU STATION SURABAYA - Qibtiyah, Mariyatul; Yuliati, Nuriah; Nurhadi, Eko (International Journal of Multidisciplinary Research and Literature, 2024)
Developing Indonesia's food and beverage business is increasing, ensuring product quality must be maintained. One of the products is Cincau Station. Cincau Station is a healthy drink made from fresh grass jelly leaves. However, the product needed a higher quality. Cincau station must have advantages; good quality products can help a business be better than other businesses. One way to increase competitive advantage is to link product quality with customer loyalty. Product quality has a very close relationship with customer satisfaction because product quality can be assessed from the product's ability to create customer loyalty. Product quality also has a positive and significant effect on customer loyalty. Customers feel that the price of Cincau Station products is affordable, and the taste of Cincau Station products is also better than other brands